2009
DOI: 10.1056/nejmoa0809171
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P-450 Polymorphisms and Response to Clopidogrel

Abstract: Among persons treated with clopidogrel, carriers of a reduced-function CYP2C19 allele had significantly lower levels of the active metabolite of clopidogrel, diminished platelet inhibition, and a higher rate of major adverse cardiovascular events, including stent thrombosis, than did noncarriers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

58
1,512
13
50

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 2,191 publications
(1,633 citation statements)
references
References 31 publications
58
1,512
13
50
Order By: Relevance
“…Although high on‐clopidogrel platelet reactivity is prevalent and associated with a higher risk of recurrent ischemic events,28, 29, 30 and several studies have shown that switching between P2Y 12 inhibitors is safe and effectively reduces platelet reactivity in patients with high on‐clopidogrel platelet reactivity,31 no randomized controlled trial has demonstrated that intensifying P2Y 12 inhibition reduces clinical end points in patients with high on‐clopidogrel platelet reactivity 12, 13, 14, 15, 16. Platelet function testing is infrequently performed in current practice,15 and recurrent ischemic events while taking clopidogrel may not necessarily reflect inadequate platelet inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Although high on‐clopidogrel platelet reactivity is prevalent and associated with a higher risk of recurrent ischemic events,28, 29, 30 and several studies have shown that switching between P2Y 12 inhibitors is safe and effectively reduces platelet reactivity in patients with high on‐clopidogrel platelet reactivity,31 no randomized controlled trial has demonstrated that intensifying P2Y 12 inhibition reduces clinical end points in patients with high on‐clopidogrel platelet reactivity 12, 13, 14, 15, 16. Platelet function testing is infrequently performed in current practice,15 and recurrent ischemic events while taking clopidogrel may not necessarily reflect inadequate platelet inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…11 The two-step activation process involving a series of cytochrome P-450 (CYP) isoenzymes, is susceptible to the interference of genetic polymorphisms and drug-drug interactions. 12,13 Proton pump inhibitors that inhibit CYP2C19, particularly omeprazole, decrease clopidogrel-induced platelet inhibition ex vivo, but there is currently no conclusive clinical evidence that co-administration of clopidogrel and proton pump inhibitors increases the risk of ischaemic events in addition, clopidogrel (and prasugrel) absorption is regulated by P-glycoprotein (encoded by ABCB1), which is an ATP-dependent efflux pump that transports various molecules across extracellular and intracellular membranes. It is expressed, among other places, on intestinal epithelial cells, where increased expression or function can affect the bioavailability of drugs that are substrates.…”
Section: Clopidogrelmentioning
confidence: 99%
“…It is an orally active drug that binds reversibly to P2Y 12 , with a stronger and more rapid anti-platelet effect than clopidogrel. 21,22 The PLATO study showed that as compared to clopidogrel, ticagrelor was associated with a 16% relative risk reduction with regard to the primary end point-a composite of death from cardiovascular causes, myocardial infarction and stroke-but no significant increase in the overall risk of major bleeding.…”
Section: Ticagrelormentioning
confidence: 99%
See 2 more Smart Citations